EUROPEAN AMBULANCE ACUTE CORONARY SYNDROME ANGIOGRAPHY (Neotložnaâ Medicinskaâ Pomoŝʹ, 2016)
Steg P.G., van ‘t Hof A., Hamm C.W., et al. Bivalirudin Startedduring Emergency Transportfor Primary PCI // N. Engl. J. Med. – 2013. Oct. 30. [Epub ahead of print].